The Mechanical Behaviors of Various Dental Implant Materials under Fatigue - Fatma Bayata; Cengiz Yildiz (Advances in Materials Science and Engineering)
The selection of materials has a considerable role on long-term stability of implants. The materials having high resistance to fatigue are required for dental implant applications since these implants are subjected to cyclic loads during chewing. This study evaluates the performance of different types of materials (AISI 316L stainless steel, alumina and its porous state, CoCr alloys, yttrium-stabilized zirconia (YSZ), zirconia-toughened alumina (ZTA), and cp Ti with the nanotubular TiO2 surface) by finite element analysis (FEA) under real cyclic biting loads and researches the optimum material for implant applications. For the analysis, the implant design generated by our group was utilized. The mechanical behavior and the life of the implant under biting loads were estimated based on the material and surface properties. According to the condition based on ISO 14801, the FEA results showed that the equivalent von Mises stress values were in the range of 226.95 MPa and 239.05 MPa. The penetration analysis was also performed, and the calculated penetration of the models onto the bone structure ranged between 0.0037389 mm and 0.013626 mm. L-605 CoCr alloy-assigned implant model showed the least penetration, while cp Ti with the nanotubular TiO2 surface led to the most one. However, the difference was about 0.01 mm, and it may not be evaluated as a distinct difference. As the final numerical evaluation item, the fatigue life was executed, and the results were achieved in the range of 4 × 105 and 1 × 109 cycles. These results indicated that different materials showed good performance for each evaluation component, but considering the overall mechanical performance and the treatment process (implant adsorption) by means of surface properties, cp Ti with the nanotubular TiO2 surface material was evaluated as the suitable one, and it may also be implied that it displayed enough performance in the designed dental implant model.